The Effect of Application Cooperative Learning Model of Think-Pair-share (TPS) and Means –End Analysis (MEA) Types on Students Learning Outcomes of Tenth Grade on Redox Material at SMA Negeri 7 Palu - Diana Natalia; Kasmudin` Mustapa; Ratman Ratman (Jurnal Akademika Kimia, 2019)
This study aimed to analyze the effect of the application of the Think-pairs-Share and Means- Ends Analysis learning Achievement of a student on reduction-oxidation in class X at SMAN 7 Palu. This study was a ween experiment with a static group pretest-posttest design. This study was carried out by holding two groups of class X Science 1 as the experimental one group (n = 25) and class X science 2 as the experimental two groups (n = 28). Results of the data analysis showed the average value (X2) of the experimental one class was 68.56 with a standard deviation of 16.97 dan (X2) of the experimental two class was 56.14 with a standard deviation of 13.12. Based on the hypothesis test results with t-test statistical of two parties obtained –ttable ≤ tcount ≥ + ttable (tcount = 1.89 and ttable = 1.67) with a significance level of α= 0.05 and degrees of freedom of 51, then Ho was rejected and Ha was accepted. It can be concluded that there was an effect of the application of the think-pairs–share and means-ends analysis learning model toward learning achievement of students in class X at SMAN 7 Palu on reduction-oxidation.